The Impact of Website Services’ Quality on Users Satisfaction in Higher Education Institutions:: A Survey among the Website Users of Economics, Commercial and Management Sciences Faculty of Ferhat Abbas University Setif1 [In Arabic] - Guechi, leila; Hebbache, Fares (Milev Journal of Research and Studies, 2022)
This study sought to determine how consumers' satisfaction is affected by the websites of higher education institutions' service quality. The study sample involved 211 users of the website of economics, commercial and management sciences faculty of Ferhat Abbas University in Setif. Primary data were gathered via a questionnaire, and they were analyzed using SPSS.26 software. The study came to the conclusion that consumers' satisfaction is positively impacted by all aspects of the website service quality. Based on these results, we provided a series of recommendations, with a focus on strengthening the safety and privacy of the faculty website, designating specific staff members to respond to users, boosting the website's functionality, and implementing ongoing changes in line with users needs.